Pemberdayaan Kader Posyandu Dalam Upaya Pencegahan Dan Pengendalian Stunting Berbasis Kearifan Lokal Di Wilayah Kerja Puskesmas Sesela Kabupaten Lombok Barat - Kamila, Nurul Auliya; Hidayati, Nurul (LPPM UNIVERSITAS NAHDLATUL WATHAN MATARAM, 2023)
The First 1,000 Days of Life (HPK) which includes pregnant women and children 0-23 months is the golden period for the most effective reduction in stunting. This is where participatory development strategies from various stakeholders, health worker and the community are really needed. This service activity is highly recommended considering that integrating the implementation of stunting prevention and control with posyandu health worker as facilitators needs to be carried out because posyandu cadres are the parties who play a very important role in carrying out early detection of stunting that occurs at the village level because their position is closer to the community. Activities in this service will be carried out in the form of counseling and training for health worker in the prevention and management of stunting in the period from pregnancy to toddlers in the form of pregnancy exercise training, early detection of baby growth and development through Denver Development Screening Test (DDST) training, KPSP (Pre-Developmental Screening Questionnaire), precise western and height measurements, filling out KMS and its interpretation as well as training in processing local food ingredients as a variation of Supplementary Feeding (PMT) for pregnant women and toddlers. This activity is aimed at cadres being able to apply their knowledge and skills to the community to socialize stunting and be able to prevent and control stunting incidents from an early age based on local wisdom. The target of this service activity is to gradually increase the knowledge and skills of cadres in preventing stunting cases in the Sesela Community Health Center Working Area, producing scientific works to be published in national seminars with ISSN and electronic mass media, as well as videos of activities that can be used for the purposes of preventing and overcoming stunting